2010
DOI: 10.1089/ast.2009.0439
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Ionizing Radiation Resistance ofDeinococcus radioduransand Antarctic Dry Valley Bacteria

Abstract: The high flux of cosmic rays onto the unshielded surface of Mars poses a significant hazard to the survival of martian microbial life. Here, we determined the survival responses of several bacterial strains to ionizing radiation exposure while frozen at a low temperature characteristic of the martian near-subsurface. Novel psychrotolerant bacterial strains were isolated from the Antarctic Dry Valleys, an environmental analogue of the martian surface, and identified by 16S rRNA gene phylogeny as representatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 105 publications
4
88
0
Order By: Relevance
“…In contrast to data from previous reports showing that frozen conditions do not offer much protection against radiation damage in D. radiodurans (166), more recent data show that D. radiodurans cells irradiated on dry ice (Ϫ70°C) have a higher gamma ray survival rate than do cells irradiated on ice or at room temperature (128,130,519). The increase in radiation resistance under frozen irradiation conditions may be due to the diminished oxygen effects on proteins (120,122).…”
Section: Ionizing Radiation Resistance Of D Radioduransmentioning
confidence: 65%
“…In contrast to data from previous reports showing that frozen conditions do not offer much protection against radiation damage in D. radiodurans (166), more recent data show that D. radiodurans cells irradiated on dry ice (Ϫ70°C) have a higher gamma ray survival rate than do cells irradiated on ice or at room temperature (128,130,519). The increase in radiation resistance under frozen irradiation conditions may be due to the diminished oxygen effects on proteins (120,122).…”
Section: Ionizing Radiation Resistance Of D Radioduransmentioning
confidence: 65%
“…Microorganism Brevundimonas sp. is known to be a resistant to UV-C, gamma radiations and hydrogen peroxide [36,37]. B. pumilus has been well known for its UVR resistance [28,32,38].…”
Section: Tolerance and Survivability Of Uvrresistant Extremophilesmentioning
confidence: 99%
“…More specifically in the interests of astrobiology, several modeling studies have involved calculation of the radiation dose profile generated by CR through the martian regolith to predict the likely survival times of spore-forming or radiation-resistant bacterial strains such as D. radiodurans in the subsurface (Mileikowsky et al, 2000;Pavlov et al, 2002;Kminek et al, 2003;Dartnell et al, 2007aDartnell et al, , 2007bDartnell et al, , 2010. While there are uncertainties in both the physics of high-energy particle transport and the biological response to irradiation, these studies broadly agree and have found that the top 20 cm of the martian surface is sterilized of even the most radiation-resistant microorganisms (based on terrestrial models such as D. radiodurans) within a million years or so, with greater survival found at increasing depths due to shielding, especially in ice deposits (Dartnell et al, 2007a).…”
Section: Sterilization Of Mars' Surfacementioning
confidence: 99%